Implementation of Management Information Systems at State Junior High School 2 Rejang Lebong Bengkulu - Mirzon Daheri (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2023)
This study aims to identify Islamic education management information systems and their concepts and implementation processes in educational institutions. A management information system is designed to provide information to support decision-making in management activities (planning, implementing, organizing and controlling) within an organization. Understanding management information systems based on information technology, including the concept of information systems, information use, and the value of information. System boundaries have been determined by encouraging the quality of the system's work. This study used a qualitative approach with a case study type, data obtained from interviews, observation, and documentation. Data analysis was carried out when the researcher came to the research locus at State Junior High School (SMPN) 2 Rejang Lebong Bengkulu; after the data was collected, analysis and conclusions were drawn. The process of credibility, dependability, confirmability and transferability is used to check the validity of the data. Research results: the work process in each system produces a result (output) that is sustainable and an evaluation system through feedback treatment. This means that if the output contains information that is contrary to the achievements of the organization, it will be input into the system; if the system has received the results of the feedback, then the system will make the necessary revisions and adjustments so that the output is consistent with its original purpose. Then, with the rapid advancement of technology, it must be tamed with an educator's ability so that technology can become a slave, not enslaved by technology.